ANALISIS PASAR SEMPURNA DAN TIDAK SEMPURNA PT.PLN MEDAN, JAMBI 1991 - Neli Mafatikun Nikmah (POLITEKNIK LP3I JAKARTA, 2020)
The market is a place where sellers and buyers meet. This study describes research on the vegetable market in Medan and the PT.PLN monopoly market in Jambi. This report presentsome data regarding the market and access to market data. The purpose of this research is the market situation, the condition of buyers and sellers, market access for new sellers and the ability of sellers to determine market prices. This research is a qualitative research with literature review through elaboration, descriptive analysis to see and examine in detail how the pattern of PT.PLN Medan and Jambi usesthe patterns in the application ofservise performance to the community and how the impact isfelt. This research still needs to be development as a medium for academic development and management-management at PT.PLN in general and PT.PLN Medan and Jambi in particular. The results showed that the implementation of a perfect and imperfect market application pattern was done intentionally unintentionally by PT.PLN Medan and Jambi as a form of application that was adjusted tothe respentive Regional Laws and Perpu so that all matters of implementation became market reaction to follow the rules and accept the consequences if they occur on the rules applied by PT.PLNKeywords: perfect market; imperefect market; price; price mechanism.